Rethinking Zimbabwean Education During and Beyond the COVID-19 Pandemic (Quest Journal of Management and Social Sciences, 2020)
Background: This paper was premised on the educational learning gap created by the COVID-19 Pandemic induced schools’ closure in Zimbabwe and the world in 2020. Approximately, 1,576 billion, 297 million and 4,6 million learners globally, in Africa and in Zimbabwe respectively, are attending schools and their learning process is interrupted because of the COVID-19 Pandemic in many different ways across the globe. Developed countries adopted innovations to ensure continuity of educational learning, however, developing countries like Zimbabwe, were caught unaware. Already battling with a crippled economy, severe natural disasters induced by climate change, this paper investigates a relatively new and demanding curriculum, the Zimbabwe education system’s capacity to adopt to the changes induced by COVID-19 Pandemic.Objective: The study has three objectives: to unearth if stakeholders are appreciative of the importance and dictates of Zimbabwe’s Competency-Based Curriculum; to ascertain if e-learning can ensure the continued provision of education during and after the COVID-19 era and other pandemics that may arise in the future; and to establish which method of education instruction is preferred by Zimbabweans, either during or after the COVID-19 Pandemic period.Methods: A mixed method research design was used to collect both qualitative and quantitative data. Considering that data collection was done at the peak of the COVID-19 period, physical contact was avoided and the research was largely hinged on an online questionnaire and interview sessions. Focus group discussions were however, also conducted when it was expedient to do so, to qualify some of the quantitative responses provided by respondents.Results: Results showed that stakeholders were inadequately consulted about the ‘new curriculum’, that education innovation to adopt e-learning is required, and that Zimbabweans prefer to have a dual method of education instruction through e-learning and in the traditional classroom set-up.Conclusions: The government needs to consult stakeholders, create synergies with partners to implement educational technologies and provide the necessary precautionary equipment in schools prior to re-opening.